(untitled) - Durham, Joel (Indianapolis, 2007)
The ultimate book on the ultimate Vista for gamers and digital media buffs. If you're the ultimate gamer and multimedia fan, Windows Vista Ultimate and this information-packed book are for you.
Keywords: Microsoft Windows (Computer file),Hệ điều hành Windows (Chương trình máy tính)